Implementation of Ornamental ART Instruction Using Modules for Eighth Grade Students at SMP Negeri 1 Jatitujuh, Majalengka Regency - Faihaa Rihhadatul’aisya Rahman; Farid Abdullah; Bandi Sobandi (Publikasi Indonesia, 2026)
The current educational era still relies heavily on conventional, teacher-centered instruction, resulting in low student engagement and limited understanding, particularly in fine arts subjects such as decorative arts. Students often imitate without grasping fundamental concepts, which hinders creativity and independent learning. This study aims to develop and assess the effectiveness of a structured decorative arts learning module designed for eighth-grade students at SMP Negeri 1 Jatitujuh, Majalengka Regency. A quantitative descriptive method with a one-group post-test design was employed, involving 29 students selected through purposive sampling. The learning module incorporated illustrations, examples, practice questions, and active learning strategies across four sessions. Data were collected via post-tests and student response questionnaires and analyzed using descriptive statistics to evaluate comprehension, application, and evaluative understanding. The results indicate a significant improvement in student understanding, with an average post-test score of 85.68, where 86.2% of students met the Minimum Competency Criteria. Student responses averaged 76.9%, reflecting the module's effectiveness, clarity, and support for independent learning. These findings demonstrate that systematic, interactive teaching materials combined with active learning methods can enhance comprehension and motivation in decorative arts. The study concludes that the module is effective in improving student understanding and provides a replicable framework for integrating student-centered learning into fine arts education.